Future supply of boreal forest ecosystem services is driven by management rather than by climate change - Triviño, María; Morán-Ordoñez, Alejandra; Eyvindson, Kyle; Blattert, Clemens; Burgas, Daniel; Repo, Anna; Pohjanmies, Tähti; Brotons, Lluís; Snäll, Tord; Mönkkönen, Mikko (Zenodo, 2022)
Forests provide a wide variety of ecosystem services (ES) to society. The boreal biome is experiencing the highest rates of warming on the planet and increasing demand for forest products. To foresee how to maximize the adaptation of boreal forests to future warmer conditions and growing demands of forest products, we need a better understanding of the relative importance of forest management and climate change on the supply of ecosystem services. Here, using Finland as a boreal forest case study, we assessed the potential supply of a wide range of ES (timber, bilberry, cowberry, mushrooms, carbon storage, scenic beauty, species habitat availability and deadwood) given seven management regimes and four climate change scenarios. We used the forest simulator SIMO to project forest dynamics for 100 years into the future (2016–2116) and estimate the potential supply of each service using published models. Then, we tested the relative importance of management and climate change as drivers of the future supply of these services using generalized linear mixed models. Our results show that the effects of management on the future supply of these ES were, on average, eleven times higher than the effects of climate change across all services but greatly differed among them (from 0.53 to 24 times higher for timber and cowberry, respectively). Notably, the importance of these drivers substantially differed among biogeographical zones within the boreal biome. The effects of climate change were 1.6 times higher in northern Finland than in southern Finland, whereas the effects of management were the opposite – they were three times higher in the south compared to the north. We conclude that new guidelines for adapting forests to global change should account for regional differences and the variation in the effects of climate change and management on different forest ES. Funding provided by: Kone Foundation Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100005781 Award Number: 201710545 Funding provided by: Norges ...